Coprinopsis afrocinerea (Agaricales, Psathyrellaceae): First record from Asia (Pakistan). Issue 10 (5th July 2022) - Ullah, Tauseef; Saba, Malka; Syed, Mahrukh Farid
Abstract: In this work, we introduced a new report, Coprinopsis afrocinerea, a coprinoid mushroom from Pakistan. This species was collected several times during the monsoon season; it was found growing on animal dung and on sandy soil mixed with wood chips and leaf litter. This taxon was identified through morphological (macro‐ and micromorphology) techniques and molecular (ITS‐region) markers. Results showed that Pakistani collection's macro‐ and micro‐morphological characters match the type specimen of Coprinopsis afrocinerea . In the phylogenetic tree, sequences of our collections fall within section Cinereae and are clustered with type sequences of Coprinopsis afrocinerea with strong statistical support. This species has already been reported from Africa and is described here for the first time from Asia. Previously, only seven species of Coprinopsis have been reported from Pakistan, and in this study, the number of known taxa has increased to eight. This paper provides a detailed morphological and molecular analysis of this species to differentiate it from closely related taxa. Abstract : Graphical representation of different techniques (Macro‐, micro‐morphological and molecular techniques) used for fungal identification.